Comparison of the outcome between cervical adenocarcinoma and squamous cell carcinoma patients with adjuvant radiotherapy following radical surgery: SGSG/TGCU Intergroup Surveillance - SHIMADA, MUNEAKI (D.A. Spandidos, 2013)
The efficacy of radiotherapy (RT) for adenocarcinoma (AC) is controversial, although patients with AC of the uterine cervix are treated in a similar manner to those with squamous cell carcinoma (SCC). This retrospective study was conducted to evaluate the efficacy of adjuvant RT for patients with AC compared to those with SCC following radical hysterectomy. A total of 820 patients with stage IB-IIB cervical cancer, who underwent type III radical hysterectomy between 1997 and 2003, were retrospectively examined; the sample included 280 patients with AC and 540 with SCC. A total of 139 patients with AC and 327 with SCC underwent adjuvant treatment. The histological type did not affect the outcome for patients with stage I disease; however, stage II patients with AC exhibited a significantly worse 5-year overall survival (OS) rate compared to those with SCC. Patients with SCC exhibited significantly higher lymph node involvement compared to those with AC in stage IB1; however, there were no differences between stages IB2 and II. Among patients with lymph node involvement, patients with AC exhibited a significantly worse 5-year survival rate compared to those with SCC (46.4 vs. 72.3%, respectively; P=0.0005). Among patients receiving adjuvant RT, those with AC recurred more frequently compared to those with SCC, particularly in the pelvic cavity, including the vaginal stump and/or pelvis (24.6 vs. 10.5%, respectively; P= 0.0022). By contrast, the histological type did not affect the incidence of recurrence in paraaortic lymph nodes and/or distant recurrence. In conclusion, RT may not suffice as an adjuvant treatment for patients with cervical AC following radical hysterectomy.